FAKTOR YANG MEMPENGARUHI BIAYA PERJALANAN WISATA PANTAI AKO DI DESA JIKUMERASA KABUPATEN BURU - Renoldy Lamberthy Papilaya; Eygner Gerald Talakua (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Travel costs are time and expenses that must be incurred by tourists to visit certain attractions. The assumption underlying the travel cost method is the expenditure of time and travel expenses incurred by someone to visit the tourist site and enjoy the tour. This study aims to identify and calculate the cost of tourist trips to Ako Beach and Analyze the factors that affect the cost of tourist trips to Ako Beach. The basic research method used is a qualitative descriptive method by collecting data through interviews using questionnaires and literature studies. The number of samples was 97 people namely 50 local tourists, 42 domestic tourists and 5 foreign tourists. And the quantitative descriptive method uses multiple linear regression analysis and calculates the total cost of the trip. The total cost of the tour on Ako Beach is Rp 169.872.500 with a total of the average cost of a tourist trip is Rp 15.283.553 based on the origin of tourists it is known that the average cost of a local tourist trip is Rp 245.360, the average cost of domestic tourist travel is Rp 2.227.393, and the average foreign tourist travel cost is Rp 12.810.800. Factors that affect the cost of travel on Ako Beach are statistically known to be income and distance.